Chicken little Walt Disney Pictures ; directed by Mark Dindal ; produced by Randy Fullmer ; story by Mark Dindal, Mark Kennedy. - Dindal, Mark; Fullmer, Randy; Kennedy, Mark (Buena Vista Pictures Distribution, 2006)
Después de arruinar su reputación en la ciudad, un pollo valeroso debe ir al rescate de sus ciudadanos vecinos cuando los alians comienzan una invasión.